Cost-effectiveness of an adjuvanted recombinant zoster vaccine in older adults in the United States who have been previously vaccinated with zoster vaccine live - Desmond Curran; Brandon J. Patterson; Desiree Van Oorschot; Philip O. Buck; Justin Carrico; Katherine A. Hicks; Bruce Lee; Barbara P. Yawn (Taylor & Francis Group, 2019)
Zoster Vaccine Live (ZVL) is marketed in the US since 2008, and a non-live adjuvanted Recombinant Zoster Vaccine (RZV) was approved in 2017. Literature suggests that waning of ZVL efficacy may necessitate additional vaccination. The Advisory Committee on Immunization Practices recommended vaccination with RZV in immunocompetent adults aged 50+ years old, including those previously vaccinated with ZVL. The objective of this study was to determine the cost-effectiveness of vaccinating US adults aged 60+ years old, previously vaccinated with ZVL. The ZOster ecoNomic Analysis (ZONA) model, a deterministic Markov model, was adapted to follow a hypothetical 1 million(M)-person cohort of US adults previously vaccinated with ZVL. Model inputs included demographics, epidemiology, vaccine characteristics, utilities and costs. Costs and quality-adjusted life-years (QALYs) were presented over the lifetimes of the cohort from the year of additional vaccination, discounted 3% annually. The model estimated that, vaccination with RZV 5 years after previous vaccination with ZVL, would reduce disease burden compared with no additional vaccination, resulting in a gain of 1,633 QALYs at a total societal cost of $96M (incremental cost-effectiveness ratio: $58,793/QALY saved). Compared with revaccinating with ZVL, vaccination with RZV would result in a gain of 1,187 QALYs and societal cost savings of almost $84M. Sensitivity, scenario, and threshold analyses demonstrated robustness of these findings. Vaccination with RZV is predicted to be cost-effective relative to no additional vaccination, assuming a threshold of $100,000/QALY, and cost-saving relative to ZVL revaccination of US adults aged 60+ years old who have been previously vaccinated with ZVL.